Exploring the link between the pediatric exposome, respiratory health, and executive function in children: a narrative review - Alcala, Cecilia S.; Lane, Jamil M.; Midya, Vishal; Eggers, Shoshannah; Wright, Robert O.; Rosa, Maria José (Frontiers in Public Health, 2024)
Asthma is a highly prevalent inflammatory condition, significantly affecting nearly six million U.S. children and impacting various facets of their developmental trajectories including neurodevelopment. Evidence supports a link between pediatric environmental exposures in two key areas: asthma and executive function (E.F.). E.F.s are a collective of higher-order cognitive processes facilitating goal-oriented behaviors. Studies also identify asthma-associated E.F. impairments in children. However, limited research has evaluated the inter-relationships among environmental exposures, asthma, and E.F. in children. This review explored relevant research to identify and connect the potential mechanisms and pathways underlying these dynamic associations. The review suggests that the role of the pediatric exposome may function through (1) several underlying biological pathways (i.e., the lung-brain axis, neuroendocrine system, and hypoxia), which could drive asthma and maladaptive E.F. in children and (2) the relationships between the exposome, asthma, and E.F. is a bidirectional linkage. The review reveals essential synergistic links between asthma and E.F. deficits, highlighting the potential role of the pediatric exposome. Accumulating scientific evidence supports a link between environmental exposures and asthma and executive function, respectively, and a link between asthma and executive function in children.  There is a gap on the evaluation of the complex synergistic link between environmental chemical exposures, asthma, and E.F. outcomes in children.  This review explores relevant research to identify and connect the potential mechanisms and pathways underlying these dynamic associations.  We will focus on the chemical exposure due to its heightened risk for children's health.